Réponses

2014-05-09T13:50:01+02:00
A = [(3x + 2) / 5] - [(5x - 7) / 2] = (-8x + 3) / 25
A =
 \frac{(3x+2)*10 - (5x-7)*25}{50} =  \frac{(-8x+3)*2}{50}
A = \frac{(30x+20) - (125x-175)}{50} = \frac{(-16x+6)}{50}
A= \frac{(30x+20) - (125x-175) - (-16x+6)}{50} = 0
A = \frac{-79x + 189}{50} = 0
A = \frac{-79x}{50} -  \frac{189}{50}  = 0
A = \frac{-79x}{50} = \frac{189}{50}
A = -79x = 189
A = 79x = -189
D'où x =  \frac{-189}{79}

Pour la deuxième, tu fais pareil, lentement, en mettant tout au même dénominateur..